Foldable displays and mobile terminal devices
The foldable display employs a hard coat film with a specific polyester base and polyimide resin cured layer to address image distortion and deformation issues, achieving high hardness and resistance to repeated folding.
Patent Information
- Application Number
- JP2024013191
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2018-05-07
- Filing Date
- 2024-01-31
- Publication Date
- 2025-04-30
- Estimated Expiration
- 2039-04-22
AI Technical Summary
Conventional foldable displays experience image distortions due to deformation of the film at the folding portion after repeated use, and they often compromise on pencil hardness to improve bending resistance.
A foldable display structure featuring a hard coat film with a polyester base film having an intrinsic viscosity of 0.65 to 1.0 dl/g, a cured layer of polyimide resin, and a hard coat layer, which provides high pencil hardness and resistance to deformation upon repeated folding.
The solution maintains high surface hardness and prevents image distortion at the folded portion, ensuring excellent durability and visibility while allowing for easy mass production.
Smart Images

Figure 0007670184000003 
Figure 0007670184000004 
Figure 0007670184000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a foldable display and a mobile terminal device, and more particularly to a foldable display and a mobile terminal device having a film surface with high hardness that is less likely to cause image distortion due to deformation of the film located on the surface even when folded repeatedly. [Background technology]
[0002] As mobile terminal devices become thinner and lighter, smartphones and other mobile terminal devices are becoming more and more popular. While mobile terminal devices are required to have a variety of functions, they are also required to be convenient. For this reason, the mobile terminal devices that are currently in use must be able to perform simple operations with one hand, and must have a small screen size of around 6 inches, since they are assumed to be stored in a pocket or the like.
[0003] On the other hand, tablet devices with screen sizes of 7 to 10 inches are highly functional and can be used not only for video content and music, but also for business purposes, drawing, reading, etc. However, they cannot be operated with one hand, are less portable, and have issues with convenience.
[0004] To achieve these goals, a method has been proposed of connecting multiple displays together to make them more compact; however, this method has not become widespread because it leaves behind a bezel, which results in the image being cut off and reduced visibility.
[0005] In recent years, mobile terminals incorporating flexible displays and foldable displays have been proposed, which provide a large-screen display without interruption to the image and are convenient to carry around.
[0006] Here, in the case of conventional displays and mobile terminal devices that do not have a folding structure, the surface of the display can be protected by a non-flexible material such as glass, but in the case of a folding display, when a one-sided display is formed via a folding part, it is necessary to use a hard coat film that is flexible and can protect the surface. However, in a folding display, the part corresponding to a certain folding part is repeatedly folded, and therefore the film in that part deforms over time, causing problems such as distorting the image displayed on the display.
[0007] A method has also been proposed in which the thickness of the folded and non-folded parts is made different; however, although the thinner film parts have improved bending resistance, there is a problem in that the pencil hardness decreases (see Patent Document 1). [Prior art documents] [Patent documents]
[0008] [Patent Document 1] JP 2016-155124 A Summary of the Invention [Problem to be solved by the invention]
[0009] The present invention seeks to solve the problems associated with conventional displays as described above, and provides a foldable display that is easy to mass-produce, has high rigidity, and is free of the risk of distortion of the image displayed at the folded part after repeated folding, and a mobile terminal device equipped with such a foldable display. [Means for solving the problem]
[0010] That is, the present invention comprises the following: 1. A foldable display having a hard coat film disposed on at least a portion of its surface, the hard coat film having a base film of a polyester film having an intrinsic viscosity of 0.65 to 1.0 dl / g, and a cured layer of a polyimide resin having a thickness of 0.5 to 3.0 μm, and a hard coat layer, in that order, on at least the surface side of the base film of the foldable display. 2. The foldable display according to claim 1, wherein the thickness of the base film is a polyester film of 10 to 75 μm. 3. The foldable display according to the above 1 or 2, wherein the hard coat layer has a thickness of 1 to 40 μm. 4. The foldable display according to any one of the above items 1 to 3, wherein a continuous single hard coat film is disposed across the folding portion of the foldable display. 5. The foldable display according to any one of the above items 1 to 4, wherein the polyester film is a biaxially stretched polyethylene terephthalate film. 6. The pencil hardness of the hard coat layer measured with a load of 750g according to JIS K5600-5-4:1999 is The foldable display according to any one of claims 1 to 5, which has a width of 2H or more. 7. The foldable display according to any one of claims 1 to 6, wherein the bending radius when folded is 5 mm or less. 8. A mobile terminal device having the foldable display according to any one of claims 1 to 7 above. Effect of the Invention
[0011] The foldable display of the present invention maintains mass productivity, and the hard coat film located on the surface does not deform after repeated folding, and the image does not become distorted at the folding portion of the high-hardness display. A mobile terminal device equipped with such a foldable display provides beautiful images, is scratch-resistant due to its high hardness, is highly functional, and is convenient in terms of portability, etc. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a schematic diagram showing the measurement points of the bending radius when folded in the present invention. [Diagram 2] 1 is a schematic cross-sectional view of one embodiment of a hard coat film of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] (display) The display in the present invention generally refers to a display device, and the types of displays include LCD, organic EL display, inorganic EL display, LED, FED, etc., but LCD, organic EL, and inorganic EL, which have a bendable structure, are preferred. In particular, organic EL and inorganic EL, which can reduce the layer structure, are particularly preferred, and organic EL, which has a wide color gamut, is even more preferred.
[0014] (Foldable display) The folding display is preferably a structure in which a single continuous display is folded in two or three or more when carried, thereby reducing the size by half or further, and improving portability. At the same time, it is desirable that the display is thin and lightweight. Therefore, the bending radius of the folding display is preferably 5 mm or less, and more preferably 3 mm or less. If the bending radius is 5 mm or less, it is possible to make the display thin when folded. It can be said that the smaller the bending radius, the better, but it may be 0.1 mm or more, or 0.5 mm or more. Even if it is 1 mm or more, the practicality is sufficiently good compared to conventional displays that do not have a folding structure. The bending radius when folded is measured at the location of the symbol 11 in the schematic diagram of FIG. 1, and means the inner radius of the folded part when folded.
[0015] (Organic EL) The general configuration of an organic EL display consists of an organic EL layer consisting of an electrode / electron transport layer / light-emitting layer / hole transport layer / transparent electrode, a retardation plate to improve image quality, and a polarizing plate.
[0016] (Mobile terminal device with touch panel) For example, when an organic EL display is used in a mobile terminal device having a touch panel, a touch panel module is disposed on the top of the organic EL display or between the organic EL layer and the retardation plate. In this case, since there is a risk of the organic EL and touch panel circuits being disconnected when an impact is applied from above, it is preferable that a film for protecting the surface is disposed. At least a part of the surface of the folding display is preferably provided with a hard coat film as a film for protecting the surface, and this preferably mainly includes the surface of the image display part of the folding display. The hard coat layer is preferably located on the outer surface side of the display.
[0017] The image display portion of the foldable display may be located on the inside or outside when folded. In other words, the hard coat film that protects the surface of the foldable display of the present invention may be located on the inside surface or the outside surface of the folded foldable display.
[0018] In the present invention, the hard coat film disposed on at least a portion of the surface of the foldable display preferably has a cured layer of polyimide resin and a hard coat layer laminated in this order on at least one side of a base film.
[0019] As the base film constituting the hard coat film, any film having high light transmittance and low haze, such as a polyimide film, a polyester film, a polycarbonate film, an acrylic film, a triacetyl cellulose film, or a cycloolefin polymer film, can be used. Among these, polyimide films and polyester films having high impact resistance and sufficient pencil hardness are preferred, and polyester films which can be produced inexpensively are particularly preferred.
[0020] Fig. 2 shows a schematic cross-sectional view of one embodiment of the hard coat film of the present invention. The hard coat film preferably has a polyimide resin cured layer (22) and a hard coat layer (23) laminated in the above order on a polyester film (21) as a base film. The hard coat film is preferably located on the surface of the foldable display, and the hard coat layer is preferably disposed so as to be located on the outer surface of the foldable display. Although not shown, it can be said that the surface of the hard coat layer (23) usually coincides with the surface of the foldable display.
[0021] In the present invention, the polyester film which is the base film of the hard coat film may be a single-layer film made of one or more polyester resins, or when two or more types of polyester are used, it may be a multilayer film or an ultra-multilayer laminate film having a repeating structure.
[0022] Examples of polyester resins include polyester films made of polyethylene terephthalate, polybutylene terephthalate, polyethylene-2,6-naphthalate, or copolymers mainly composed of the components of these resins. Among these, biaxially stretched polyethylene terephthalate films are particularly preferred in terms of mechanical properties, heat resistance, transparency, cost, etc.
[0023] When a polyester copolymer is used for the base film, examples of the dicarboxylic acid component of the polyester include aliphatic dicarboxylic acids such as adipic acid and sebacic acid; aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, phthalic acid, and 2,6-naphthalenedicarboxylic acid; and polyfunctional carboxylic acids such as trimellitic acid and pyromellitic acid. Examples of the glycol component include fatty acid glycols such as ethylene glycol, diethylene glycol, 1,4-butanediol, propylene glycol, and neopentyl glycol; aromatic glycols such as p-xylene glycol; alicyclic glycols such as 1,4-cyclohexanedimethanol; and polyethylene glycols having an average molecular weight of 150 to 20,000. The mass ratio of the copolymerization components of the preferred copolymer is less than 20% by mass. When it is less than 20% by mass, the film strength, transparency, and heat resistance are maintained, which is preferable.
[0024] In addition, in the production of polyester film, the intrinsic viscosity of at least one type of resin pellet is preferably in the range of 0.65 to 1.0 dl / g. When the intrinsic viscosity is 0.65 dl / g or more, the obtained film is less likely to deform after repeatedly folding, and there is no risk of image quality being deteriorated, which is preferable. On the other hand, when the intrinsic viscosity is 1.00 dl / g or less, the filtration pressure of the molten fluid does not increase too much, and film production can be easily and stably operated, which is preferable.
[0025] Regardless of whether the film is a single-layered or laminated film, the intrinsic viscosity of the film is preferably 0.65 dl / g or more. More preferably, it is 0.68 dl / g or more. If it is 0.65 dl / g or more, sufficient bending resistance effect can be obtained. On the other hand, a film having an intrinsic viscosity of 1.00 dl / g or less is preferable because it can be produced with good operability.
[0026] The thickness of the polyester film is preferably 10 to 75 μm, and more preferably 25 to 75 μm. A thickness of 10 μm or more is preferable because it is easy to obtain an improvement in pencil hardness. On the other hand, a thickness of 75 μm or less is preferable because it is advantageous for weight reduction and is excellent in flexibility, processability, handleability, etc.
[0027] The surface of the polyester film in the present invention may be smooth or uneven, but since it is used for display surface covering, the deterioration of optical properties due to unevenness is not preferable. The haze is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably as small as possible, but it may be 0.1% or more, or 0.3% or more.
[0028] As mentioned above, in order to reduce haze, it is better for the unevenness of the film surface to be not too large. However, in order to provide a certain degree of slipperiness from the viewpoint of ease of handling, unevenness can be formed by blending a filler into the surface polyester resin layer or by coating a coat layer containing a filler during the film formation process.
[0029] The method of blending the particles into the polyester film can be a known method. For example, the particles can be added at any stage of polyester production, but preferably, the particles can be added as a slurry dispersed in ethylene glycol or the like at the stage of esterification, or after the completion of the transesterification reaction, and before the start of the polycondensation reaction, to proceed with the polycondensation reaction. The particles can also be blended with a slurry of the particles dispersed in ethylene glycol or water or the like and the polyester raw material using a vented kneading extruder, or with a method of blending dried particles and the polyester raw material using a kneading extruder.
[0030] Among them, a method is preferred in which aggregated inorganic particles are homogeneously dispersed in a monomer liquid that will become a part of the polyester raw material, and then the filtered product is added to the remainder of the polyester raw material before, during, or after the esterification reaction. According to this method, since the monomer liquid has a low viscosity, homogeneous dispersion of the particles and highly accurate filtration of the slurry can be easily performed, and when added to the remainder of the raw material, the dispersibility of the particles is good and new aggregates are unlikely to be generated. From this viewpoint, it is particularly preferred to add to the remainder of the raw material in a low temperature state before the esterification reaction.
[0031] In addition, the number of protrusions on the film surface can be further reduced by a method in which, after obtaining a polyester containing particles in advance, the pellets are mixed and extruded with pellets not containing particles (master batch method).
[0032] The polyester film may contain various additives, such as antistatic agents, UV absorbers, and stabilizers, within the range that satisfies the light transmittance.
[0033] The total light transmittance of the polyester film is preferably 85% or more, and more preferably 87% or more. If the transmittance is 85% or more, visibility can be sufficiently ensured. Although it can be said that the higher the total light transmittance of the polyester film, the better, it may be 99% or less, or 97% or less.
[0034] The surface of the polyester film of the present invention may be subjected to a treatment for improving adhesion to a resin forming a cured layer of a polyimide resin or the like.
[0035] Examples of the surface treatment method include roughening treatment using sandblasting or solvent treatment, and oxidation treatment such as corona discharge treatment, electron beam irradiation treatment, plasma treatment, ozone or ultraviolet irradiation treatment, flame treatment, chromic acid treatment, or hot air treatment, and any of these methods can be used without any particular limitation.
[0036] Although not shown in Fig. 2, it is also preferable that an easy-adhesion layer is laminated on the polyester film, and the adhesion can be improved by an adhesion improving layer such as an easy-adhesion layer. The easy-adhesion layer can be made of any resin, such as an acrylic resin, a polyester resin, a polyurethane resin, or a polyether resin, without any particular limitation, and can be formed by a general coating method, preferably a so-called in-line coating method.
[0037] The polyester film described above can be produced, for example, through a polymerization step in which inorganic particles are homogeneously dispersed in a monomer liquid that becomes a part of the polyester raw material, the dispersion is filtered, and then the dispersion is added to the remainder of the polyester raw material to polymerize the polyester, and a film formation step in which the polyester is melt-extruded through a filter into a sheet, which is cooled and stretched to form a base film.
[0038] Next, a method for producing a polyester film will be described in detail using an example in which polyethylene terephthalate (hereinafter, sometimes referred to as PET) pellets are used as the raw material for the base film, but the method is not limited thereto. In addition, the number of layers is not limited to a single layer or a multilayer structure.
[0039] After mixing and drying PET pellets in a predetermined ratio, the mixture is fed to a known melt lamination extruder, extruded from a slit die into a sheet, and cooled and solidified on a casting roll to form an unstretched film. In the case of a single layer, one extruder is sufficient, but in the case of producing a film with a multilayer structure, two or more extruders, two or more manifolds or merging blocks (e.g., merging blocks having a rectangular merging portion) are used to laminate multiple film layers constituting each outermost layer, and a sheet of two or more layers is extruded from a die and cooled on a casting roll to form an unstretched film.
[0040] In this case, it is preferable to perform high-precision filtration to remove foreign matter contained in the resin at any location where the molten resin is kept at about 280° C. during melt extrusion. The filter material used for high-precision filtration of the molten resin is not particularly limited, but a filter material made of sintered stainless steel is preferable because it has excellent performance in removing aggregates and high-melting organic matter mainly composed of Si, Ti, Sb, Ge, and Cu.
[0041] Furthermore, the filtration particle size (initial filtration efficiency 95%) of the filter medium is preferably 20 μm or less, particularly preferably 15 μm or less. If the filtration particle size (initial filtration efficiency 95%) of the filter medium exceeds 20 μm, foreign matter with a size of 20 μm or more cannot be sufficiently removed. By using a filter medium with a filtration particle size (initial filtration efficiency 95%) of 20 μm or less to perform high-precision filtration of molten resin, productivity may decrease, but it is preferable to obtain a film with few protrusions due to coarse particles.
[0042] Specifically, for example, PET pellets are thoroughly vacuum-dried, then fed to an extruder, melt-extruded into a sheet at about 280°C, and cooled and solidified to form an unstretched PET sheet. The unstretched sheet obtained is stretched 2.5 to 5.0 times in the longitudinal direction with a roll heated to 80 to 120°C to obtain a uniaxially oriented PET film. Furthermore, the end of the film is held by a clip and introduced into a hot air zone heated to 80 to 180°C, dried, and then stretched 2.5 to 5.0 times in the width direction. Subsequently, the film is introduced into a heat treatment zone at 160 to 240°C, where heat treatment is performed for 1 to 60 seconds to complete the crystal orientation. During this heat treatment process, a relaxation treatment of 1 to 12% may be performed in the width direction or longitudinal direction as necessary.
[0043] (Polyimide resin hardened layer) The polyester film positioned on the surface of the foldable display to protect the display preferably has a cured layer of polyimide-based resin between the polyester film and the hard coat layer. The polyimide-based resin preferably includes a polyimide resin or a polyamide-imide resin, and is preferably a resin having a reactive functional group. The reactive functional group is preferable because it forms a crosslinked structure, improves the elastic modulus of the coating film, and improves the pencil hardness.
[0044] Polyimide resins are also available in the form of a solution, such as "Polyamic Acid Type Polyimide Resin - HCI Series" manufactured by Hitachi Chemical Co., Ltd. and "Neoprim (registered trademark)" manufactured by Mitsubishi Gas Chemical Co., Ltd. Examples of polyamide-imide resin solutions include "Viromax (registered trademark)" manufactured by Toyobo Co., Ltd. and "Polyamide-imide Resin - HPC Series" manufactured by Hitachi Chemical Co., Ltd.
[0045] (Crosslinking agent) It is also preferable to use a crosslinking agent in combination to harden the polyimide resin. The crosslinking agent may be an isocyanate crosslinking agent, an epoxy crosslinking agent, a chelate crosslinking agent, an aziridine crosslinking agent, an oxazoline crosslinking agent, or the like, without any particular limitation.
[0046] (Additives) In addition, additives such as an adhesion improving material for improving adhesion to the hard coat layer and an ultraviolet absorbing agent for improving light resistance, as well as fillers, etc. may also be added.
[0047] (Film thickness) The thickness of the cured layer of the polyimide resin is preferably 0.5 to 3 μm. If the thickness is 0.5 μm or more, the effect of improving the pencil hardness becomes significant, which is preferable. Also, if the thickness is 3 μm or less, the effect of improving the pencil hardness becomes significant without decreasing the bending resistance, which is preferable.
[0048] (Application method) The method for applying the cured layer of the polyimide resin can be any method including a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.
[0049] (Curing conditions) The polyamideimide layer can be cured by a method suitable for the crosslinking agent, such as by using energy rays such as ultraviolet rays or electron beams, or by using heat. In the case of curing by heat, the temperature is preferably 150° C. or less, and particularly preferably 130° C. or less.
[0050] (Hard coat layer) The polyester film that is placed on the surface of the foldable display to protect the display preferably has a hard coat layer on the surface. The resin that forms the hard coat layer can be any resin, including (meth)acrylate, siloxane, inorganic hybrid, urethane (meth)acrylate, polyester (meth)acrylate, and epoxy, without any particular limitation. Two or more types of materials can be mixed and used, and particles such as inorganic filler or organic filler can be added.
[0051] (Film thickness) The thickness of the hard coat layer is preferably 1 to 40 μm. When the thickness is 1 μm or more, good pencil hardness is obtained, which is preferable. When the thickness is 40 μm or less, curling due to cure shrinkage of the hard coat is suppressed, and the handling property of the film can be improved.
[0052] (Application method) The hard coat layer can be applied by any method including, but not limited to, a Mayer bar, a gravure coater, a die coater, a knife coater, etc., and can be appropriately selected depending on the viscosity and film thickness.
[0053] (Curing conditions) The hard coat layer can be cured by energy rays such as ultraviolet rays and electron beams, or by heat, but ultraviolet rays and electron beams are preferred in order to reduce damage to the film.
[0054] (Pencil hardness) The pencil hardness of the hard coat layer of the hard coat film is preferably 2H or more, more preferably 3H or more. If the hard coat layer has a pencil hardness of 2H or more, it is not easily scratched and does not reduce visibility. In general, the pencil hardness of the hard coat layer is preferably high, but it may be 10H or less, 8H or less, or even 6H or less can be used without any practical problems.
[0055] (Type of hard coat layer) The hard coat layer in the present invention may have other functions added thereto, so long as it can be used for the purpose of increasing the pencil hardness of the surface and protecting the display as described above.For example, hard coat layers with added functions such as antiglare layers, antiglare antireflection layers, antireflection layers, low reflection layers, and antistatic layers having a certain pencil hardness as described above are also preferably used in the present invention.
[0056] The haze of the hard coat film in the present invention is preferably 3% or less, more preferably 2% or less, and most preferably 1% or less, similar to that of the polyester film. If the haze is 3% or less, the visibility of the image can be improved. The lower limit of the haze is preferably as small as possible, but it may be 0.1% or more, or 0.3% or more.
[0057] The total light transmittance of the hard coat film in the present invention is preferably 85% or more, more preferably 87% or more, similar to that of the polyester film. If the transmittance is 85% or more, visibility can be sufficiently ensured. Although it can be said that the higher the total light transmittance, the better, it may be 99% or less, or 97% or less. EXAMPLES
[0058] Next, the effects of the present invention will be described using examples and comparative examples. First, the evaluation methods of the characteristic values used in the present invention will be described below.
[0059] (1) Intrinsic viscosity The film or polyester resin was crushed and dried, and then dissolved in a mixed solvent of phenol / tetrachloroethane = 60 / 40 (mass ratio). After the solution was centrifuged to remove inorganic particles, the flow time of a solution with a concentration of 0.4 (g / dl) at 30°C and the flow time of the solvent alone were measured using an Ubbelohde viscometer, and the intrinsic viscosity was calculated from the time ratio using the Huggins formula and assuming that the Huggins constant is 0.38. In the case of a laminated film, the intrinsic viscosity of each layer alone was evaluated by scraping off the corresponding polyester layer of the film according to the laminate thickness.
[0060] (2) Flexibility A sample with a size of 50 mm in the width direction × 100 mm in the flow direction is prepared. Using a no-load U-shaped stretch tester (Yuasa System Co., Ltd., DLDMLH-FS), the bending radius is set to 3 mm, and the sample is bent 50,000 times at a speed of 1 time / second. At that time, the sample is fixed at a position 10 mm from both ends of the long side, and the bending portion is 50 mm × 80 mm. After the bending process is completed, the sample is placed on a flat surface with the inside of the bend facing down, and visually inspected. In each of the following examples and comparative examples, the bending resistance of the hard coat film is evaluated. The hard coat layer is bent so as to face the outside of the bend, and evaluated. ◎: No deformation of the sample was observed. ○: The sample was deformed, but the maximum floating height was less than 5 mm when placed horizontally. ×: The sample has a crease or the maximum height of the sample when placed horizontally is 5 mm or more.
[0061] (3) Pencil hardness The hard coat layer of the hard coat film was measured at a load of 750 g and a speed of 0.5 mm / s in accordance with JIS K 5600-5-4:1999.
[0062] (4) Total light transmittance, haze Measure the haze of the hard coat film using a haze meter (NDH5000, manufactured by Nippon Denshoku Industries Co., Ltd.) did.
[0063] (5) Thickness of polyester film Three 5 cm square samples were cut out from three randomly selected points on the film. Measurements were taken at five points on each sample (total of 15 points) using an electric micrometer (Fine Leaf, Millitron 1245D), and the average value was taken as the thickness of the polyester film.
[0064] (6) Thickness of the cured layer of the polyimide resin and the thickness of the hard coat layer Sections were cut from three randomly selected locations of the hard coat film. One edge surface per section was homogenized using a microtome. The edge was observed at 600x magnification using a digital microscope RH-2000 (Hirox Corporation), and the thickness of the cured polyimide resin layer and the thickness of the hard coat layer were measured at five points per edge (total of 15 points), and the average value of each was calculated.
[0065] (Preparation of polyimide resin coating solution 1) 100 parts by weight of a polyamideimide resin solution (manufactured by Toyobo Co., Ltd., Viromax (registered trademark) HR-15ET, solids concentration 25%) and 2.5 parts by weight of a crosslinking agent (manufactured by Mitsubishi Gas Chemical Co., Inc., product name: Tetrad X, solids concentration: 100% by weight) were mixed and diluted with a solvent of toluene / MEK = 1 / 1 to prepare coating solution 1 with a concentration of 15%.
[0066] (Preparation of hard coat coating solution 2) 95 parts by weight of urethane acrylate hard coating agent (Beamset (registered trademark) 577, solid content concentration 100%, manufactured by Arakawa Chemical Industries, Ltd.), photoradical polymerization initiator (IGMResi 5 parts by weight of Omnirad907 (manufactured by ns Co., Ltd., product name: Omnirad907, solids concentration: 100% by weight) and 0.1 parts by weight of a leveling agent (BYK307 (manufactured by BYK Japan Co., Ltd., solids concentration: 100%) were mixed and diluted with a solvent of toluene / MEK = 1 / 1 to prepare coating solution 1 with a concentration of 40%.
[0067] (Preparation of polyethylene terephthalate pellets (a)) A continuous esterification reactor consisting of a three-stage complete mixing tank having an agitator, a partial condenser, a raw material inlet, and a product outlet was used as the esterification reactor, and the slurry was continuously fed to the first esterification reactor of the esterification reactor with TPA at 2 tons / hr, EG at 2 moles per mole of TPA, and antimony trioxide at an amount such that Sb atoms were 160 ppm relative to the produced PET, and reacted at normal pressure for an average residence time of 4 hours at 255°C. Next, the reaction product in the first esterification reactor was continuously taken out of the system and fed to the second esterification reactor, and EG distilled from the first esterification reactor was fed to the second esterification reactor at 8% by mass relative to the produced polymer (produced PET), and further, an EG solution containing magnesium acetate in an amount such that Mg atoms were 65 ppm relative to the produced PET and an EG solution containing TMPA in an amount such that P atoms were 20 ppm relative to the produced PET were added, and reacted at normal pressure for an average residence time of 1.5 hours at 260°C. Next, the reaction product in the second esterification reactor was continuously taken out of the system and fed to a third esterification reactor, and an EG solution containing TMPA in an amount such that the P atom was 20 ppm relative to the produced PET was added, and the reaction was carried out at normal pressure for an average residence time of 0.5 hours at 260° C. The esterification reaction product produced in the third esterification reactor was continuously fed to a three-stage continuous polycondensation reactor to carry out polycondensation, and further filtered with a stainless steel sintered filter medium (nominal filtration accuracy of 90% cut of 5 μm particles) to obtain polyethylene terephthalate pellets (a) with an intrinsic viscosity of 0.62 dl / g.
[0068] (Preparation of polyethylene terephthalate pellets (b)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (b) having an intrinsic viscosity of 0.67 dl / g.
[0069] (Preparation of polyethylene terephthalate pellets (c)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (c) having an intrinsic viscosity of 0.75 dl / g.
[0070] (Preparation of polyethylene terephthalate pellets (d)) The polyethylene terephthalate pellets (a) were subjected to solid-phase polymerization at 220° C. for various times under a reduced pressure of 0.5 mmHg using a rotary vacuum polymerization apparatus to produce polyethylene terephthalate pellets (d) having an intrinsic viscosity of 0.83 dl / g.
[0071] The polyethylene terephthalate master pellets (a) were dried under reduced pressure (3 Torr) at 180°C for 8 hours, and then the polyethylene terephthalate pellets (a) were extruded into an extruder. The polymer was fed to a feeder and melted at 285°C. The polymer was filtered through a stainless steel sintered filter medium (nominal filtration accuracy 10μm particles 95% cut), extruded from a die in the form of a sheet, and then contacted with a casting drum with a surface temperature of 30°C using an electrostatic casting method to cool and solidify, producing an unstretched film. The unstretched film was stretched 3.4 times in the longitudinal direction at 85°C. The uniaxially stretched film was stretched 4.2 times in the transverse direction at 95°C using a tenter, and heat-treated at 220°C for 5 seconds to obtain the polyethylene terephthalate film No. 1 in Table 1. The polyethylene terephthalate master pellets (b) to (d) were fed to a process similar to that described above, except for some adjustments to the conditions, to obtain the polyethylene terephthalate films No. 2 to 5 in Table 1.
[0072] Example 1 Polyimide resin coating solution 1 was applied to one surface of polyethylene terephthalate film No. 3 using a Mayer bar so that the film thickness after drying would be 2.0 μm, and then dried at 120° C. for 1 minute to obtain a cured layer of polyimide resin. Next, hard coat coating solution 2 was applied to the cured layer of polyimide resin using a Mayer bar so that the film thickness after drying would be 10 μm, and after drying at 80° C. for 30 seconds, ultraviolet light was irradiated (accumulated light amount 200 mJ / cm 2 ) to obtain a hard coat film.
[0073] (Examples 2 to 5, Comparative Examples 1 to 3) A hard coat film was prepared under the conditions in Table 2 in the same manner as in Example 1.
[0074] The prepared film was attached to an organic EL module via a 25 μm thick adhesive layer, and a smartphone-type folding display that can be folded in half at the center of the entire display with a radius of 3 mm, which corresponds to the bending radius in FIG. 1, was prepared. The hard coat film is arranged on the surface of one continuous display through the folding portion, and the hard coat layer is arranged so as to be located on the surface of the display. The hard coat films of each embodiment were satisfactory in terms of operation and visibility as a smartphone that can be folded in half at the center and carried around. On the other hand, the folding displays using the hard coat films of Comparative Examples 2 and 3 were not very preferable, as it seemed that image distortion occurred at the folding portion of the display as the frequency of use increased. In addition, Comparative Example 1 was somewhat unsatisfactory in terms of the pencil hardness of the hard coat film.
[0075] [Table 1]
[0076] [Table 2] [Industrial Applicability]
[0077] According to the present invention, it is possible to provide a foldable display that has a high pencil hardness on the surface while maintaining mass productivity, is less likely to cause deformation of the surface hard coat film after repeated folding, and is less likely to cause image distortion over time, and a mobile terminal device equipped with such a foldable display. [Explanation of symbols]
[0078] 1: Foldable display 11: Bending radius 2: Hard coat film 21: Polyester film 22: Polyimide resin hardened layer 23: Hard coat layer
Claims
[Claim 1] A folding organic electroluminescence display comprising an organic electroluminescence module and a hard coat film, the hard coat film being disposed on at least a part of a surface thereof, The hard coat film is disposed on an upper portion of an organic electroluminescence module, The hard coat film has a polyethylene terephthalate film as a base film, and has an easy-adhesion layer, a cured layer, and a hard coat layer in this order on at least the front surface side of the base film of the foldable organic EL display, The easy-adhesion layer contains any one of an acrylic resin, a polyester resin, a polyurethane resin, and a polyether resin, the cured layer contains either a polyimide resin or a polyamide-imide resin; The hard coat layer contains a urethane acrylate resin, The bending radius when folded is 5 mm or less, In a no-load U-shaped stretch test, the hard coat layer was bent 50,000 times at a bending radius of 3 mm and a speed of 1 time per second so that the hard coat layer faced the outside of the bend. After bending, the hard coat layer was placed horizontally on a flat surface with the inside of the bend facing down. The maximum lift is less than 5 mm, or there is no deformation. Foldable OLED display.
Citation Information
Patent Citations
Colored hard coat film
JP2002258760A
Hard coat film
JP2006231845A
Flame-retardant polyester film for electric storage element electrode, electrode for electric storage element comprising the same, and electric storage element comprising the same
JP2011174009A
Optical film, resin material for optical film, and image display device
JP2013114198A
Acrylic copolymer, biaxial stretched film, polarizer and liquid crystal display device
JP2015025136A